Humanities for college students / Singapore river walk and jubilee walk (Singapore : Straits Times Press and the National Heritage Board, 2018)
Filled with evocative archival photographs and vivid snapshots of the modern city, Singapore Trails: Singapore River Walk & Jubilee Walk uncovers the island$1 (Bs rich past and vibrant present via two meticulously-curated walking trails. This handy guidebook brings together two trails in the heart of the city: the Singapore River Walk, which traces Singapore$1 (Bs path from a bustling 19th-century port to a modern city, and the Jubilee Walk, created to mark Singapore$1 (Bs Golden Jubilee in 2015. Developed by the National Heritage Board, these storied paths take readers on a journey not simply through Singapore$1 (Bs civic district, but through her rich and multifaceted past. With this guide in hand, tourists, foreign residents, and locals alike will enjoy finding out more about Singapore on foot.s
Singapore river walk -- Jubilee walk -- Bibliography&credits -- The Singapore river walk -- A harbour of history -- Points of arrival -- Commerce on the waterfront -- Supporting connections -- Centres of community, service and devotion -- Art by the river -- Singapore river walk map.
Includes bibliographical references and index.
Keywords: TRAILS -- SINGAPORE